1999
DOI: 10.1089/10430349950018571
|View full text |Cite
|
Sign up to set email alerts
|

Successful Culture and Sustainability in Vivo of Gene-Modified Human Oral Mucosal Epithelium

Abstract: Human oral mucosal cells are an attractive site for tissue engineering because they are the most accessible cells in the body and easy to manipulate in vitro. They thus have possibilities for targeting by somatic gene therapy. We examined the efficiency of retrovirus-mediated gene transfer and the construction of mucosal epithelium in vivo. Human oral mucosal cells were transduced with a retroviral vector carrying the lacZ gene at high efficiency and constructed epithelium after G418 selection with 3T3 cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…17,18 A similar approach has also been developed for the replacement of oral mucosa, although this procedure has not yet been marketed. 19,20 The engineering and transplantation of oral mucosa and gingiva could be potentially important as a new technique in periodontal graft surgery and in the treatment of gingival recession.…”
Section: Skin and Oral Mucosamentioning
confidence: 99%
“…17,18 A similar approach has also been developed for the replacement of oral mucosa, although this procedure has not yet been marketed. 19,20 The engineering and transplantation of oral mucosa and gingiva could be potentially important as a new technique in periodontal graft surgery and in the treatment of gingival recession.…”
Section: Skin and Oral Mucosamentioning
confidence: 99%
“…The increased availability and use of tissue-engineered oral epithelium has led to a need for more special or ideal functions. Previously, we reported a successful technique for making gene-modified tissue-engineered oral epithelium with retrovirus-mediated gene transduction and confirmed that tissue-engineered oral epithelium is an ideal target tissue for gene therapy (5). The potential for using the tissue-engineered oral epithelium as an alternative material for delivering active drugs has attracted considerable interest in recent years.…”
Section: Discussionmentioning
confidence: 77%
“…Mizuno et al (5) reported success in making genemodified cultured human oral epithelium with retrovirusmediated gene transduction. Although viral based vectors have gained wide acceptance, serious concerns have been voiced about the use of viral vectors, such as viral toxicity, host immune rejection and difficult preparation.…”
Section: Introductionmentioning
confidence: 99%
“…were infected with a retroviral vector carrying the b-gal or human clotting factor IX gene, which is able to promote wound healing and to prevent excess bleeding (Mizuno et al 1999). Next, the cells were cultured on a mitomycin C-treated 3T3 feeder layer to make a stratified epithelial sheet.…”
Section: Wound Healing Human Oral Mucosal Keratinocytesmentioning
confidence: 99%